Analisis Kebutuhan Multimedia Komik Digital untuk Mengatasi Rendahnya Hasil Belajar IPA di SDN 7 Sugihwaras - Yunita Dewi Nur Rohmah; Farida Nurlaila ZunaidahZunaidah; Tutut Indah Sulistyowati (Lembaga Yasin AlSys, 2026)
Low active student engagement and the suboptimal understanding of food chain concepts due to the use of conventional learning methods at SDN 7 Sugihwaras indicate the need to develop learning media that are more visual, interactive, and contextual. This study aims to analyze the needs for developing digital comic multimedia as an effort to improve Grade V students’ learning outcomes on food chain material. This study used a Development Studies approach at the needs analysis stage (preliminary) within Tessmer’s formative evaluation model. Data were collected through observation, semi-structured interviews, and a pre-test involving 31 students and were then analyzed to identify learning conditions, media availability, and initial learning achievement. The results showed three main findings, namely that science learning still fully relied on lectures and textbooks, technology-based digital learning media were not yet available, and the abstract concept of food chains had not been adequately visualized. The pre-test results showed an average score of 72.19, with 16 of 31 students, or 51.6%, not yet achieving mastery. The conclusion of this study affirms the actual need to develop digital comic multimedia based on the “RANTAIKU” application using Articulate Storyline 3, which can integrate text, images, animation, and interactive quizzes. These findings provide practical implications for the development of digital learning media contextualized within four local ecosystems, namely rice fields, forests, seas, and rivers, as a solution to overcome the limitations of conventional learning on food chain material in elementary schools.